Usefulness of Trabecular Metal Cones in Revision Total Knee Arthroplasty in a Korean Population: A Case Series - Baek JH; Lee SC; Ryu S; Ahn HS; Nam CH (Orthopedic Research and Reviews, 2022)
Ji-Hoon Baek,1 Su Chan Lee,1 Suengryol Ryu,2 Hye Sun Ahn,1 Chang Hyun Nam1 1Joint & Arthritis Research, Department of Orthopaedic Surgery, Himchan Hospital, Seoul, Republic of Korea; 2Department of Orthopaedic Surgery, Himnaera Hospital, Busan, Republic of KoreaCorrespondence: Chang Hyun Nam, Joint & Arthritis Research, Department of Orthopaedic Surgery, Himchan Hospital, 120, Sinmok-ro, Yangcheon-gu, Seoul, 07999, Republic of Korea, Tel +82-2-3219-9229, Fax +82-2-2061-8605, Email himchanhospital@gmail.comPurpose: The purpose of this study was to assess the medium-term results of trabecular metal cones for the reconstruction of large bone defects in revision TKA.Methods: Thirteen patients who had undergone revision TKA using trabecular metal cones for femoral and/or tibial large bone defects were identified. We included patients who had a minimum of three years follow-up in the study. We evaluated their functional outcomes, implant survivorship, radiological findings, and complications.Results: At a mean follow-up of 6.9 years (range of 3.5– 9.4 years), all trabecular metal cones and implants were well fixed and did not exhibit any radiographic evidence of migration or loosening. At the final follow-up, the mean Knee Society knee scores had improved from 37.2 to 78.1 (p < 0.05), and function scores had improved from 35.5 to 77.5 points (p < 0.05). One intraoperative fracture in the distal femur occurred in an 85-year-old woman during impaction of a single trabecular metal cone. The fracture was successfully affixed to the femoral cone and bone three months postoperatively.Conclusion: The present study of trabecular metal cones demonstrates excellent clinical outcomes and survivorship in revision TKA during medium-term follow-up periods. However, longer-term follow-up studies are needed to further investigate these implants in revision TKA. Additionally, the necessity of metal cones in revision procedures should be carefully considered depending on patient needs and economic capabilities.Keywords: total knee arthroplasty, trabecular metal cone, outcome, survivorship